Fabrication of layer-by-layer assembled FO hollow fiber membranes and their performances using low concentration draw solutions - Liu, Chang (2013)
Great efforts from the membrane community have been devoted in developing suitable membranes for forward osmosis (FO) applications in recent years. In the current study, the layer-by-layer (LBL) polyelectrolyte assembly technique has been successfully applied onto a microporous polyethersulfone (PES) hollow fiber substrate to make novel LBL hollow fiber membranes suitable for FO process for the first time. The FO performance of the LBL hollow fibers with different numbers of deposited layers has been evaluated using deionized (DI) water as the feed and MgCl2 solution of various concentrations as the draw solution in both orientations. With 6 layers deposited and in the active layer facing draw solution (AL-facing-DS) orientation, the membrane showed high water fluxes of 14.6, 25.9 and 40.5 L/m2 h with corresponding salt to water flux, Js/Jv, ratio of 0.034, 0.066 and 0.201 g/L using 0.05, 0.1 and 0.5 M draw solution, respectively. These promising results demonstrate the potential application of the LBL hollow fibers in FO process using low concentration draw solutions, which can substantially reduce the draw solution replenishment, and the energy consumption for draw solution regeneration and separation.